Zakat Pekerja Digital Menurut Fatwa MUI dalam Perspektif Maqashid al-Syariah Imam al-Syathibi - Ulum, Bachrul (TAWAZUN: Journal of Sharia Economic Law, 2025)
The phenomenon of income from digital activities is becoming increasingly important in the era of the industrial revolution 4.0. Including the obligation to carry out zakat effectively and in accordance with Islamic law. The review of Maqashid al-Syariah Imam al-Syathibi from the results of the Ijtima Ulama of the MUI Fatwa Commission is used in this study to provide zakat solutions in the current modern era. The aim is to understand more deeply about the suitability of the MUI fatwa with the principles of Maqashid al-Syariah Imam al-Syathibi and to assess the concept of digital can be applied fairly, relevantly and beneficially for digital workers in the era of a technology-based economy. This research uses library analysis methods to collect data on sharia economic law literature as well as works that examine Imam al-Syathibi's Maqashid al-Sharia theory. Qualitative analysis was performed on the data to determine how these principles are used in the context of zakat on digital income. The results of the study show that income from digital work as an object of zakat, determining the appropriate nisab and haul, and applying a zakat rate of 2.5% are actions that are consistent with Maqashid al-Shariah.